2000
DOI: 10.1128/jcm.38.9.3150-3155.2000
|View full text |Cite
|
Sign up to set email alerts
|

Role of IS6110-Targeted PCR, Culture, Biochemical, Clinical, and Immunological Criteria for Diagnosis of Tuberculous Meningitis

Abstract: An open prospective clinical, microbiological, and molecular analysis of a national molecular diagnostic service for tuberculous meningitis (TBM) using an in-house IS6110-targeted PCR for molecular “Fastrack” diagnosis was carried out. Between April 1997 and June 1998. Consecutive cerebrospinal fluid (CSF) samples from 131 patients were assessed. Against a culture on the same sample, PCR had a sensitivity of 75% and a specificity of 94%. Of samples from patients classified as definite or probable TBM cases bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(33 citation statements)
references
References 24 publications
0
30
1
2
Order By: Relevance
“…The results of PCR studies in the CSF have shown a 94-100% specificity but sensitivities ranging from 75% to 100%. [19][20][21][22] Variations in the PCR methodologies have been attempted to improve the sensitivity and specificity of the test. Primers targeting regions other than the insertional sequence IS6110 have been used.…”
Section: Introductionmentioning
confidence: 99%
“…The results of PCR studies in the CSF have shown a 94-100% specificity but sensitivities ranging from 75% to 100%. [19][20][21][22] Variations in the PCR methodologies have been attempted to improve the sensitivity and specificity of the test. Primers targeting regions other than the insertional sequence IS6110 have been used.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PCR studies are heterogeneous concerning sample preparation and target sequence amplification and therefore not comparable. Reported sensitivities for the diagnosis of TBM ranged from 32% to 100% with specificities ranging from 89% to 100% (12–16). The CSF PCR for TBM is rapid and therefore of value when clinical suspicion is high, but results have to be interpreted in context with clinical and other laboratory findings and treatment should not be withheld on the basis of a negative PCR result.…”
Section: Discussionmentioning
confidence: 99%
“…This MTBC‐specific insertion sequence is commonly used as a target in NAATs for detecting MTBC. The IS 6110 (IS 986 ) segments that have frequently been used include the 123‐bp (78–83, 95), 158‐bp (84), 181‐bp (85, 86), 200‐bp (87), 215‐bp (88), 245‐bp (89), 263‐bp (90, 93), 325‐bp (91) and 541‐bp (16, 92) fragment. Both single‐ and nested‐PCR systems have been used, and detection was done by simple agarose electrophoresis, autoradiograms or hybridisation assays.…”
Section: Molecular Detection Of Mtbcmentioning
confidence: 99%